A formulação da política externa brasileira e as novas lideranças políticas regionais - Mariano, Karina L. Pasquariello [UNESP]; Mariano, Marcelo Passini (Universidade Estadual Paulista (Unesp), 2008)
Este artigo demarca a intensificação das pressões sobre as condições tradicionais de formulação e implementação das decisões no campo da política externa. A análise permite compreender melhor o aumento da tensão sobre as condições que garantem uma situação de continuidade e previsibilidade da atuação externa brasileira. Nesse sentido, o governo Lula não é a causa dessa pressão por mudança, mas sua lógica governamental contribui para intensificar e acelerar essas pressões.

This article discusses the rising of demands to change the traditional conditions of making decisions in the Brazilian foreign policy. The analysis allows understanding the increase of the tension on the conditions that guarantee continuity and previsibility of the Brazilian external performance. Finally, it examines that Lula’s government isn’t the reason of this pressure, but how its governmental logical contributes to rise and speed up these tensions.
The formulation of Brasilian foreign policy and the new regional political leaders
Keywords: Política Externa brasileira; Ministério das Relações Exteriores; Governo Lula; Brazilian foreign policy Itamaraty; Ministry of External Relations; Lula’s government